My Name is Bill W. [videorecording (DVD)] - Woods, James, 1947-; Williams, JoBeth; Sinise, Gary; Coe, George (Warner Home Video, 2006)
World War I veteran William Wilson has everything: loving wife, good health, Wall Street career --and a "drinking problem." Penniless overnight when the stock market crashes, Bill quickly descends into a stormy sea of booze. Then he meets Bob Smith, an Ohio surgeon with the same "problem." Together they discover a way to stay sober --one day at a time, and their mutual triumph would soon become the world's.